IMAGINING THE ENDS OF IDENTITY: BIRTH AND DEATH ON INSTAGRAM - Leaver, Tama; Highfield, Tim (AoIR Selected Papers of Internet Research, 2015)
While social media is communal by definition, the use, regulation and understanding of social media is frequently limited to individuals (even if those individuals add together as a group or community of some kind). In this paper, we detail an attempt to examine how the visual social media app and platform Instagram is used to imagine the relationships with those who have no self-representational agency: babies and the recently deceased. Specifically, the #ultrasound and #funeral hashtags were tracked for three months in 2014. The aim is to utilise this mapping to investigate how relationships appear in visual form, and what these then say about these dynamics are presented visually, and are thus imagined, by Instagram users. Building on Instagram mapping methods we have detailed in depth elsewhere (xxxx), using the Instagram API we tracked media in which the media item’s caption included specific hashtags (whilst initially returned by the Instagram API, we disregarded media with the hashtag when the tag was not added by the initial poster, but rather by a subsequent commenter). While all Instagram metadata and media captured and analysed was completely public in a technical sense, the public/private distinction at the level of code is insufficient; rather, following Markham and Buchanan (2012) we were mindful of not amplifying media content that may not have been shared with this intention, and have chosen not to include example images in this published form.